Brat [compact disc, unabridged] : an '80s story - McCarthy, Andrew, 1962- (Hachette Audio, 2021)
Most people know Andrew McCarthy from his movie roles in Pretty in Pink, St. Elmo's Fire, Weekend at Bernie's, and Less than Zero, and as a charter member of Hollywood's Brat Pack. The iconic group of ingenues and heartthrobs that included Rob Lowe, Molly Ringwald, Emilio Estevez, and Demi Moore, has come to represent both a genre of film and an era of pop culture. In his memoir, McCarthy focuses his gaze on that singular moment in time. The result is a revealing look at coming of age in a maelstrom, reckoning with conflicted ambition, innocence, addiction, and masculinity. New York City of the 1980's is brought to vivid life in these pages, scoring loose joints in Washington Square Park and skipping school in favor of the cinema where he fell in love with the movies. Filled with personal revelations of innocence lost to heady days in Hollywood with John Hughes and an iconic cast of characters, this is an intimate story of an outsider caught up in a most unwitting success.